Draft Genome Sequence of Campylobacter fetus MMM01, Isolated from a Chronic Kidney Disease Patient with Sepsis - Rohit, Anusha (Genome Announc, 2015)
Campylobacter fetus is a Gram-negative bacterium that has caused several cases of human and animal disease. Here, we report the draft genome sequence of C. fetus MMM01, isolated from the blood of a 60-year-old patient with type II diabetes and chronic kidney disease. The sequence has a total length of 1,740,393 bp and an average G+C content of 33.1%. The availability of the draft genome sequence of C. fetus MMM01 isolated from a case of chronic kidney disease will contribute to a better understanding of the pathophysiological mechanisms of this organism.